Peran Mekanisme Corporate Governance dan Profitabilitas terhadap Tax Avoidance - Irwan Prasetyo; Juli Riyanto Triwijaya (STIE PENA, 2026)
The purpose of this study is to investigate how corporate governance practices and profitability affect tax evasion in manufacturing firms between 2022 to 2025. Return on Equity (ROE) is used to quantify profitability, and independent commissioners, audit committees, and institutional ownership are among the corporate governance measures examined. Using secondary data from the annual reports of industrial businesses listed on the Indonesia Stock Exchange (IDX), this study employs a quantitative methodology. All manufacturing companies listed on the IDX make up the population, and 24 companies' criteria were used to choose the sample using purposive sampling. Descriptive statistics, multiple linear regression analysis, hypothesis testing, coefficient of determination, and traditional assumption tests are some of the data analysis methods that are employed. The study's findings show that while independent commissioners and audit committees have no effect on tax avoidance, institutional ownership and profitability (ROE) have a major impact. Profitability and corporate governance procedures both have a significant impact on how manufacturing companies dodge taxes.